Development of a real-time duplex PCR assay for simultaneously diagnosis of KHV and CEV in common carp and koi - Khumaira Puspasari; Adityawati Fajar Rini; Noviana Dewi; Ratih Ismayasari (Jurnal Akuakultur Indonesia)
Koi herpesvirus (KHV) and carp edema virus (CEV) are potential risks for the koi trade and for global common carp aquaculture. Due to the severe impact of both viruses, a robust diagnostic tool was required, capable of detecting and distinguishing both infections with high accuracy and precision. The aim of this study was to describe a real-time duplex TaqMan PCR assay for simultaneous detection of KHV and CEV in common carp and koi. Two pairs of primers with two TaqMan probes were used to amplify specific and conserved regions of KHV and CEV DNA. This assay was confirmed to be sensitive and specific. Limit of detections of the assay were 15 DNA copies/µL for KHV and 150 DNA copies/µL for CEV, respectively. This assay was able to identify and distinguish CEV and KHV, but was unable to identify other pathogens and sample matrices. For clinical validation, 18 KHV and CEV positive samples each, as well as 12 negative samples were tested with three different test methods, i.e., real-time duplex PCR, real-time simplex PCR, and conventional PCR. All three tests provide optimal conformity of results. The results showed that real-time duplex PCR was able to detect the presence and distinguish each pathogen in infected fish. This real-time duplex PCR assay is a rapid, sensitive, and specific test for detecting KHV and CEV in carp fish, thus it can be considered a valid alternative assay in aquaculture clinical laboratories.